Mener la recherche avec les sujets concernés : comment et pour quels résultats ? - Gilles Monceau; Marguerite Soulière (Éducation et Socialisation)
The Francophone international network Recherche avec supports the development of research that involves participation of subjects touched by the research. Besides international and interdisciplinary meetings, the network develops via a website, information and educational tools for the dissemination of its work and questionings. Its reflections are about ethical, epistemological and methodological issues in the research process. The article shows how the network is a device whose primary quality is to engage its members through a continuous reflexivity process about how they develop and conduct their research with the people concerned by it. It also shows what types of results it produces. The goal is not to produce recommendations for a better way to do research but an analytical framework applicable to the action research, intervention research, collaborative research, participatory research, socio-clinical research and other approaches that involve the subjects concerned by the research object.